A Model of Sustainable Waste Management Based on Climate Village Program in Pasaran Island, Lampung Province, Indonesia - Cahya Alam, Firdha; Mawaddah, Nurul; Sahid; Ulya Bunga, Venny; Arwieny Hanami, Zarah; Prayogo, Wisnu; Kamal, Mushthofa; Awfa, Dion; Meisya Ruth, Gabriella Meisya Ruth; Simanullang, Lillis; Gultom, Tiara (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Research focuses on waste management challenges on Pasaran Island, Bandar Lampung, examining waste generation, composition, and stakeholder involvement. Data was collected through solid waste sampling, interviews, questionnaires, and documentation, following the SNI-19-3694-1994 standard. A sample size of 20 households was determined using the Slovin formula, and 10 stakeholders from various sectors were selected for analysis. The study used the Analytic Hierarchy Process (AHP) to identify an effective waste management model aligned with the Climate Village Program. The analysis highlighted key factors such as maintenance ease, community participation, and pollution control. Among the alternatives, a household-scale model involving sorting, composting, waste banks, and the House of Recycling Innovation (RINDU) emerged as the most suitable. The findings suggest that enhancing waste management facilities like waste banks and RINDU would support the Ministry of Environment and Forestry’s programs and align with local regulations. This study offers insights that could benefit other small islands or communities facing similar waste management challenges.